A longitudinal investigation of the effects of language instruction versus immersion on cognitive functions in young adult Chinese speakers learning English. Issue 1 (2nd March 2023) - Xia, Lihua; Bak, Thomas H.; Vega-Mendoza, Mariana; Sorace, Antonella
Abstract: The current study examined cognitive effects of two pathways of second language (L2) acquisition longitudinally in Chinese speakers learning English in an L2-dominant environment. Thirty-nine participants who attended an intensive 10-week English course (L2-instruction group) were compared to 38 participants who attended regular university courses taught in English (L2-immersion group). Four repeated assessments were conducted over 10 weeks: precourse (baseline) and postcourse assessments, and two interim assessments every 3 weeks. Both groups matched on background variables (e.g., intelligence) and showed comparable cognitive performance in all measures at the baseline. The longitudinal results showed a similar improvement in both groups for most cognitive measures, such as visual and auditory inhibition. The only significant group difference was observed in the auditory inhibition test, where the L2-instruction group outperformed the L2-immersion group. Taken together, our results suggest a specific effect of language experience and an overall effect of linguistic context on cognitive functions.